Developing a Causally Valid Picture-Story Measure of Sexual Motivation: I. Effects of Priming - Hinzmann, Jessica; Khalaidovski, Ksenia; Kullmann, Jennifer S.; Brummer, Julian; Braun, Sinja; Kurz, Petra; Wagner, Katharina M.; Schultheiss, Oliver (Motivation Science, 2023)
Sexual motivation plays a crucial role in both normal sexual functioning as well as sexual dysfunctions. Although many self-report questionnaires exist to assess sexual motivation, their validity is restricted in that their sensitivity to experimental manipulation has not been tested and that they are subject to self-report limitations (e.g., self-representational issues). The aim of the current research is to develop and validate through experimental means a measure of sexual motivation based on the content analysis of imaginative stories that participants write about socially ambiguous pictures. In two studies (Study 1: N = 86; Study 2: N = 113), participants were randomly allocated to an erotic prime or control prime condition and took a picture-story test before and after the presentation of the primes. Subjective affect was assessed in both studies; physiological measures of affect (pupillometry and facial electromyography) and a criterion measure of sexual motivation (key-pressing for longer exposure to sexual vs. control pictures) only in Study 2. In both studies, erotically primed participants showed an increase of sexual imagery in picture stories, whereas participants presented with control primes did not. In Study 2, this effect was mediated by subjective and physiological arousal. Sexual imagery changes also mediated the effect on the behavioral criterion (viewing time for sexual pictures). We additionally report evidence for the discriminant validity of the sexual motive arousal procedure.
CRIS-Team Scopus Importer:2024-12-16
Keywords: causal validation; picture-story exercise; priming; sexual motivation